2004
DOI: 10.1128/jvi.78.20.11425-11428.2004
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by Morphine of Viral Set Point in Rhesus Macaques Infected with Simian Immunodeficiency Virus and Simian-Human Immunodeficiency Virus

Abstract: Six rhesus macaques were adapted to morphine dependence by injecting three doses of morphine (5 mg/kg of body weight) for a total of 20 weeks. These animals along with six control macaques were infected intravenously with mixture of simian-human immunodeficiency virus KU-1B (SHIV KU-1B ), SHIV 89.6P , and simian immunodeficiency virus 17E-Fr. Levels of circulating CD4؉ T cells and viral loads in the plasma and the cerebrospinal fluid were monitored in these macaques for a period of 12 weeks. Both morphine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
80
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 15 publications
3
80
0
1
Order By: Relevance
“…These findings suggest that morphine may increase both HIV binding to and infection of PBMCs and may be astrocytes (Mahajan et al 2002;Steele et al 2003). Studies of SIV-infected macaques that received morphine demonstrated increased CCR5 expression on PBMCs, as well as increased viral replication in the CNS (Suzuki et al 2002;Kumar et al 2004). …”
Section: Morphinementioning
confidence: 94%
“…These findings suggest that morphine may increase both HIV binding to and infection of PBMCs and may be astrocytes (Mahajan et al 2002;Steele et al 2003). Studies of SIV-infected macaques that received morphine demonstrated increased CCR5 expression on PBMCs, as well as increased viral replication in the CNS (Suzuki et al 2002;Kumar et al 2004). …”
Section: Morphinementioning
confidence: 94%
“…Opiate abuse has been shown to increase inflammatory events within the CNS (Anthony et al, 2004;Arango et al, 2004). Recent findings indicate that chronic opiate abuse increases simian immunodeficiency virus (SIV)/simian-human immunodeficiency virus (SHIV) load in the serum and cerebrospinal fluid (CSF) of nonhuman primates (Kumar et al, 2004) and significantly worsens CD4…”
Section: Introductionmentioning
confidence: 99%
“…2,3,6,7 In addition, in vitro and in vivo studies have demonstrated a correlation between drugs of abuse and increased viral replication. [8][9][10][11][12][13][14] We have developed a reproducible nonhuman primate model of IDU and HIV disease that utilizes a neuropathogenic SIV (SIV=17E-Fr) and two SHIVs (SHIV KU1-B and SHIV 89.6 P) in Indian rhesus macaques. 13,14 The use of these three viruses leads to massive CD4 þ T cell loss and neurological disorders mimicking comparable clinical manifestations in humans.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14] We have developed a reproducible nonhuman primate model of IDU and HIV disease that utilizes a neuropathogenic SIV (SIV=17E-Fr) and two SHIVs (SHIV KU1-B and SHIV 89.6 P) in Indian rhesus macaques. 13,14 The use of these three viruses leads to massive CD4 þ T cell loss and neurological disorders mimicking comparable clinical manifestations in humans. Briefly, morphine dependence was established by injecting increasing doses of morphine (1-5 mg=kg of body weight over a 2-week period) by the intramuscular route at 8-h intervals.…”
mentioning
confidence: 99%